Co-occurrence of JAK2-V617 F mutation and BCR::ABL1 translocation in chronic myeloproliferative neoplasms: a potentially confounding genetic combination - Zanelli, Magda; Bisagni, Alessandra; Sanguedolce, Francesca; Broggi, Giuseppe; Fragliasso, Valentina; Zizzo, Maurizio; Palicelli, Andrea; Martino, Giovanni; Cresta, Camilla; Caprera, Cecilia; Corsi, Matteo; Gentile, Pietro; et al. (Frontiers in Oncology, 2024)
Myeloproliferative neoplasms (MPNs) are classified into Philadelphia (Ph) chromosome–positive chronic myeloid leukemia (CML) and Ph-negative MPNs. BCR::ABL1 translocation is the key genetic event of CML, whereas JAK2/MPL/CALR mutations are molecular aberrations of Ph-negative MPNs. Despite initially considered mutually exclusive genetic aberrations, the co-occurrence of BCR::ABL1 and JAK2 has been reported in a limited number of cases. The two genetic alterations may be identified either at the same time or JAK2 aberration may be detected in patients with a previous CML treated with tyrosine kinase inhibitors or, finally, BCR::ABL1 translocation occurs in patients with a history of JAK2-positive MPN. This combination of genomic alterations is potentially confounding with clinical manifestations often misinterpreted either as disease progression or drug resistance, therefore leading to inappropriate patient’s treatment. Our systematic review aims to improve hematologist and pathologist knowledge on this rare subset of patients. Starting from the presentation of two additional cases from our routine daily practice, we focus mainly on clinical, laboratory, and bone marrow histological findings, which may represent useful clues of BCR::ABL1 and JAK2 co-occurrence. The interaction between JAK2 and BCR::ABL1 clones during the disease course as well as therapy and outcome are presented.